THE EFFECT OF SNAKEHEAD FISH (CHANNA STRIATA) CONSUMPTION IN ACCELERATING PERINIUM WOUND HEALING - Sri Susilawati; Meti Patimah; Melsa Sagita Imaniar (Siklus : Journal Research Midwifery Politeknik Tegal, 2021)
A perineum tear is an obstetric tear in the perineum area due to the muscles' inability and soft tissues to accommodate the fetus's birth. WHO reported 90% of women experienced perineum tear during spontaneous labor. If the wound took a long time to heal, there would be discomfort such as pain and fear of moving. To help wound healing, the mother could consume snakehead fish (Channa Striata). This study aims to determine the effect of snakehead fish's consumption (Channa Striata) on the acceleration of perineal wound healing. The quantitative research method with quasi-experiments posttest only controls group design was used in this study. Respondents of this study were postpartum mothers who had first and second-degree perineal injuries. The respondent was given intervention in the form of consuming snakehead fish. Wound healing speed data was carried out by observation. The study obtained a p-value of 0.000, it can be concluded that Ho was rejected and Ha accepted. This indicates a significant influence of snakehead fish's consumption (Channa Striata) on the acceleration of perineum wound healing in the postpartum mother. Keyword: postpartum, snakehead fish, perineum wounds